Exploring the complex relationships between coping strategies, locus of control and self-esteem with psychopathology: structural equation modeling with a special focus on clinical high-risk of psychosis - Rinaldi, Giulia; Osman, Naweed; Kaess, Michael; Schimmelmann, Benno; Kindler, Jochen; Schultze-Lutter, Frauke; Michel, Chantal (European psychiatry, 2023)
BackgroundCoping strategies, competence, and locus of control (LOC) beliefs are important predictors of mental health (MH). However, research into their complex interactions has produced mixed results. Our study investigated them further in the previously unexplored context of clinical high-risk (CHR) of psychosis.MethodsWe tested six alternative structural equation models in a community sample (N = 523), hypothesizing a mediating role of coping and treating CHR symptoms as (i) an additional mediator or (ii) a specific outcome. Our measurement model included two latent factors of MH: (1) psychopathology (PP), consisting of presence of mental disorders, global and psychosocial functioning, and (2) self-rated health (SRH) status.ResultsIn the model with the best Akaike Information Criterion and the latent factors as outcome variables, maladaptive coping completely mediated the impact of maladaptive LOC on PP and SRH. Additionally, CHR symptoms partially mediated the effect of maladaptive coping on PP and SRH in the community sample, as long as sex was not entered into the model. In the clinical sample (N = 371), the model did not support a mediation by CHR symptoms, despite significant pathways with both coping and MH outcomes; further, competence beliefs directly impacted SRH.ConclusionsCoping strategies are an important intervention target for MH promotion, especially in the community. In clinical populations, interventions focusing on coping strategies may improve CHR symptoms, thus potentially supporting better MH, especially SRH. Additionally, due to their mostly cascading effects on MH, improving competence and LOC beliefs may also promote psychological well-being.